2012
DOI: 10.4161/onci.21285
|View full text |Cite
|
Sign up to set email alerts
|

Functional differences between low- and high-affinity CD8+T cells in the tumor environment

Abstract: Weak T-cell antigen receptor (TCR)-ligand interactions are sufficient to activate naïve CD8+ T cells, but generally do not result in tumor eradication. How differences in TCR affinity affect the regulation of T-cell function in an immunosuppressive tumor environment has not been investigated. We have examined the functional differences of high- vs. low-affinity CD8+ T cells and we observed that infiltration, accumulation, survival and cytotoxicity within the tumor are severely impacted by the strength of TCR-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 40 publications
0
65
2
Order By: Relevance
“…Although our study demonstrates that provision of CD4 help preferentially augmented TCR hi T cells both in vitro and in vivo, Sherman and colleagues (14,32) reported that tumor Ag-specific CD4 + T help increased expansion as well as effector functions of both high-and low-avidity tumor Ag-specific CD8 + T cells, which resulted in tumor eradication. In those studies, both CD4 + and CD8 + T cells recognized a surrogate tumor Ag that was expressed as a transgene by an autochthonous tumor.…”
Section: Discussioncontrasting
confidence: 57%
“…Although our study demonstrates that provision of CD4 help preferentially augmented TCR hi T cells both in vitro and in vivo, Sherman and colleagues (14,32) reported that tumor Ag-specific CD4 + T help increased expansion as well as effector functions of both high-and low-avidity tumor Ag-specific CD8 + T cells, which resulted in tumor eradication. In those studies, both CD4 + and CD8 + T cells recognized a surrogate tumor Ag that was expressed as a transgene by an autochthonous tumor.…”
Section: Discussioncontrasting
confidence: 57%
“…Reports have shown that stronger TCR:pMHC interactions generate superior effector functions in mice (19,(33)(34)(35) and humans (36)(37)(38). However, the impact of TCR/CD8:pMHC avidity on CD8 T cell differentiation and clonotype repertoire selection within the periphery remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…42 These low-and high-avidity immune cells have the capacity to expand and exert killing functions on leukemic cells as shown in vitro and in animal models postvaccination. 12,54,55 The exploitation of donor-derived autoimmunity against selected TAAs by improving donor selection and facilitating adoptive immunotransfer of donor-derived T lymphocytes may significantly contribute to the control of the malignant disease in the absence of GVHD after allotransplantation, where an optimal environment offers unique opportunities for homeostatic expansion. 11,56 The presence of the target antigen represents an essential condition for the persistence of the TAA-specific immune responses, as suggested by the studies in the course of pregnancy.…”
Section: Discussionmentioning
confidence: 99%